Peran Humas dalam Membentuk Opini Publik di Madrasah Aliyah Bilingual Junwangi Sidoarjo - Fathul Fauzi; Abdullah; Onik Zakiyyah; Ulfah Nurrohmah; Putri Almaas Harmelia; Poppy Widyastuti (Kariman: Jurnal Pendidikan Keislaman, 2023)
Public relations or what can be called public relations is very much needed in an educational institution, especially in communicating with the community to form an opinion or a good image. This type of research is a qualitative descriptive research. Data collection techniques using interviews, observation, and documentation. Then the data is analyzed through data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of the role of public relations in shaping public opinion in Madrasah Aliyah Bilingual Junwangi includes the role of public relations as a communicator, the role of public relations as a relationship builder, the role of public relations as backup management and the role of public relations as forming public opinion. delivery of information to alumni, delivery of information to society and government, visits from guardians of students. The manifestation of the role of public relations as a relationship builder includes: socialization of mutaba'ah guardians of students (institutional meetings with guardians of students) its functions are for program socialization, Islamic boarding school socialization, sowan, final class socialization, graduation SOP socialization. or public opinion including: socialization of PPDB, informing about paid activities, outreach on social media. The role of public relations as back-up management is an activity carried out by public relations through several processes, namely the process of finding facts, then planning by communicating and then making an evaluation. Public Relations MA Bilingual Junwangi also uses several types of communication media in carrying out its activities, both direct and indirect communication media.